Pengaruh Konsentrasi Bubuk Kulit Manggis Terhadap Mutu Gula Merah Kelapa Sawit (Elaeis guineensis Jacq.) - Mutia, Reiza; Prendika, Wimpy; Prasetyo, Rahmat Joko (Badan Riset dan Inovasi Daerah Kabupaten Pelalawan, 2023)
The replanting activity caused problems at the oil palm farmer level: the high cost of replanting and the loss of farmer’s income during the period. The solution offered is to exploit the sap obtained from the oil palm trunk into brown sugar which has economic value. The characteristic of sap which is easily contaminated by the microbe, requires a good preservative to maintain the quality of brown sugar produced. This research used natural preservatives (P) derived from mangosteen fruit skin with preservative concentrations: control, 6%, 9%, and 12% b/v. the observed parameters are pH value, total dissolved solids, water content, ash content, sugar reduction, total sugar, and organoleptic quality. The results showed that natural preservative treatment with a concentration of 9% and storage for 8 hours is the best treatment for maintaining pH value and total dissolved solids. The results of the brown sugar quality test include water content, ash content, total sugar, and organoleptic quality to color, aroma, taste, and texture by the quality standards of SNI 01-3743-1995. The best treatment based on chemical tests and organoleptic quality is P1, a concentration of 6%, producing brown sugar with the closest quality to the standard SNI 01-3743-1995.